The Effect of Live Streaming Content Quality on Purchase Intent Through Storytelling on Shopee Live - Sauptika Kancana; Rich Simeon Siagian (Universitas Budi Luhur, 2026)
The use of live streaming as a digital marketing strategy in e-commerce has been widely adopted by businesses; however, its effectiveness in driving purchase intention largely depends on how the content is delivered to consumers. This study aims to analyze the effect of live streaming content quality on purchase intention, with storytelling as an intervening variable on Shopee Live of Erigo Official Shop. This research employs a quantitative approach using probability sampling with a simple random sampling method. The sample consists of 86 respondents, who are active students of Business Administration at UPN “Veteran” Yogyakarta (batch 2022–2023) who have watched the Shopee Live streaming of Erigo Official Shop. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (SmartPLS 4.0). The results indicate that live streaming content quality has a positive and significant effect on storytelling, and storytelling significantly influences purchase intention. However, live streaming content quality doesn’t have a direct effect on purchase intention; instead, it affects purchase intention indirectly through storytelling as an intervening variable. This study concludes that storytelling plays a crucial mediating role in enhancing the effectiveness of live streaming marketing. The limitation of this research lies in its focus on a single brand and platform, which restricts the generalizability of the findings. Therefore, future research is recommended to involve multiple brands and platforms. Managerially, businesses are advised to integrate high-quality content with strong storytelling techniques to improve the effectiveness of live streaming strategies.